173k views
0 votes
Complete the solution of the equation. Find the

value of y when x equals -12.
-6x - 3y = 57

User Tana
by
5.3k points

2 Answers

0 votes

Answer:

Y=5

Explanation:

x = -12( given)

-6 X( -12) -3y = 57

72-3y = 57

-3y=57-72

-3y= -15

Y=-15/-3

Y=5

User Panagiotis Simakis
by
5.4k points
4 votes

Answer:


y=5

Explanation:

we have the expression:


-6x - 3y = 57

and we are told that
x=-12, so we must substitute this value in the previous equation and then clear for the variable y:

substituting x:


-6(-12)-3y=57

clearing for y:


72-3y=57\\-3y=57-72\\-3y=-15\\y=(-15)/(-3)\\ y=5

and we can corroborate this result by substituting the values in the original equation


-6(-12)-3(5)=72-15=57

User Vamsi Emani
by
5.7k points